Robustly correlated key‐medical image for DNA‐chaos based encryption - Ichraf Aouissaoui; Toufik Bakir; Anis Sakly (IET Image Processing, 2021)
Abstract Medical images include confidential and sensitive information about patients. Hence, ensuring the security of these images is a crucial requirement. This paper proposes an efficient and secure medical image encryption‐decryption scheme based on deoxyribonucleic acid (DNA), one‐dimensional chaotic maps (tent and logistic maps), and hash functions (SHA‐256 and MD5). The first part of the proposed scheme is the key generation based on the hash functions of the image and its metadata. The key then is highly related and intensely sensitive to the original image. The second part is the rotation and permutation of the first two MSB bit‐plans of the medical image to reduce its black background that produces redundant DNA encoded sequences. The third part is the DNA encoding‐decoding using dynamically chosen DNA rules for every 2‐bit pixel value through the logistic map. Meanwhile, the confusion‐diffusion is performed using the tent map and XOR operation. Simulation results and security analysis prove the good encryption effects of the proposed scheme compared to the state‐of‐art methods with a correlation of 6.66617e‐7 and a very large key space of 2624. Furthermore, the proposed system has a strong ability to resist various common attacks such as chosen/known‐plaintext attacks and cropping/noise attacks.